Draft Annual State Plan 2012-2013 West Bengal - Planning Commission (Planning Commission, 2012)
Year 2012-13 is the first year of 12th Plan period. The basic objective for the 12th plan is fester, more inclusive and sustainable growth. In our State, during the XIth Plan period, the average annual production of food grains was 154 lakh M.T. while the cropping intensity has been in the range of 182% which is far behind the target fixed at the onset of the XIth plan. The annual average production growth of food grains registered a negative trend (-4.38%) during last four years.
State Planning Department, Government of West Bengal
Government of West Bengal